Analisis Komunikasi Interpersonal untuk Meningkatkan Kinerja Pegawai pada Dinas Kependudukan dan Pencatatan Sipil Kabupaten Karawang - Jodi Dwi Lesmana; Sungkono; Maman Mulya Karnama (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of the research is to determine, analyze and explain the impact of interpersonal communication on employee performance at the Population and Civil Registration Service of Karawang Regency. Using qualitative methods with interview, observation and documentation techniques, this research reveals that interpersonal communication plays a crucial role in achieving optimal performance. Key elements such as openness, empathy, positive attitudes, and orientation towards others are the main focus in daily interactions in the work environment. Even though employee performance has been recognized with awards from the West Java Province Population and Civil Registration Service, this research also identified the problem of frequent miscommunication, which can hinder work effectiveness. Employee competency development programs, such as "Dukcapil Belajar," have been proven to contribute to improving performance. The results of this research emphasize the importance of effective interpersonal communication to support organizational success and suggest that efforts to improve interpersonal communication continue to be made to minimize miscommunication and support the achievement of organizational goals.